A Escola Invisível: artes plásticas em Fortaleza 1928-1958 - Lima, Roberto Galvão (2004)
We seek, in this study, includes the development of artistic activity in Fortaleza between 1928 and 1958, focusing on some of the numerous faces possible to spread the modernist artistic values ​​of the capital of Ceará.